On multi-fiber beam model with coupled axial and bending response - Casaux-Ginestet, Géraldine; Ibrahimbegovic, Adnan (European Journal of Computational Mechanics, 2011)
Being able to reproduce the coupling between normal and flexural components is a crucial point for multifiber beam element modeling. The aim of this work is to propose a solution for this coupling, using the incompatible modes method. Applied to axial interpolation functions, this method makes possible the coupled description of normal and flexural responses with the same order of accuracy. The enrichment is presented in detail then its performances are highlighted thanks to an academic test.